2021
DOI: 10.1029/2021gl094581
|View full text |Cite
|
Sign up to set email alerts
|

Spring‐Fall Asymmetry in VLF Amplitudes Recorded in the North Atlantic Region: The Fall‐Effect

Abstract: Very low frequency (VLF: 3-30 kHz) radio waves propagate inside the Earth-ionosphere waveguide monitoring the electrical conductivity of its boundaries. The upper boundary properties of the waveguide can be represented by Wait parameters (Wait & Spies, 1964), namely, the reference height and conductivity gradient of the D-region. The quiescent ionospheric condition can be disturbed by different types of physical phenomena, originating in space (Clilverd et al., 2010;Macotela et al., 2017) or on Earth (Macotela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…Though there are several case studies and periodic campaigns carried out to explore the D-region electron density variations and their causative mechanisms, we are still lacking to address the seasonal variation of D-region studies using continuous observations. A recent study by Macotela et al (2021) reported that during the fall equinox, there is an increase in the noontime mean amplitude of VLF radio waves in high and mid-latitudes, which do not resemble the solar zenith angle (see Fig. 3).…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…Though there are several case studies and periodic campaigns carried out to explore the D-region electron density variations and their causative mechanisms, we are still lacking to address the seasonal variation of D-region studies using continuous observations. A recent study by Macotela et al (2021) reported that during the fall equinox, there is an increase in the noontime mean amplitude of VLF radio waves in high and mid-latitudes, which do not resemble the solar zenith angle (see Fig. 3).…”
Section: Introductionmentioning
confidence: 91%
“…Thus, they postulate that the changes in the collision frequency associated with the background temperature could be a prime reason for the observed increase in the noontime VLF amplitude. It is well known that the VLF radio waves are drastically affected by the D-region electron density, however, Macotela et al (2021) did not consider the electron density role (if any) on the fall effect. Therefore, this study focuses to explore the altitudinal, and seasonal variation of noontime electron number density using partial reflection radar observations from 2014 to 2022 at a high-latitude location.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have also used differences in Hough modes and vertical wavelengths to understand the changes in the SW2 latitudinal variation with altitude (e.g., Azeem et al, 2016;Stober et al, 2021;. In addition, signals of distinct September transitions are observed in the D-region ionosphere in the propagation of very low frequency (VLF) radio wave signals (Macotela et al, 2021), suggesting an association with the mean temperature variation at 70-80 km and the semidiurnal solar tidal enhancement.…”
Section: Introductionmentioning
confidence: 99%